Method for producing sulfide solid electrolyte
The use of fluorine-containing solvents in the production of sulfide solid electrolytes addresses the handling and environmental issues of traditional organic solvents, enhancing safety and conductivity for industrial applications in solid-state batteries.
Patent Information
- Application Number
- JP2023503838
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-05
- Filing Date
- 2022-02-28
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2042-02-28
AI Technical Summary
Existing methods for producing sulfide solid electrolytes using organic solvents like toluene and heptane are difficult to handle and pose environmental risks due to their flammability and water reactivity, making them unsuitable for industrial-scale production.
A method involving the use of fluorine-containing solvents for wet pulverization and drying processes to produce sulfide solid electrolytes, which includes mixing lithium, phosphorus, and sulfur sources, followed by firing and pulverization in an inert atmosphere, to enhance safety and reduce environmental impact.
The method enables the production of sulfide solid electrolytes with improved lithium ion conductivity and reduced environmental footprint, using safer and less flammable fluorine solvents, facilitating their use in solid-state batteries.
Smart Images

Figure 0007609967000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a sulfide solid electrolyte. The sulfide solid electrolyte produced by the method of the present invention is useful, for example, as an electrolyte for solid-state batteries. [Background technology]
[0002] In recent years, solid electrolytes have been attracting attention as an alternative to the electrolytes used in many liquid batteries. Solid-state batteries using solid electrolytes are safer than liquid batteries that use flammable organic solvents, and are expected to be put to practical use as batteries with high energy density.
[0003] A sulfide solid electrolyte is known as one of the solid electrolytes. Since the sulfide solid electrolyte is highly reactive with water, when the sulfide solid electrolyte is made into a slurry, an aromatic organic solvent such as toluene, which is an organic compound that is difficult to mix with water, or an aliphatic organic solvent such as heptane is used as a dispersion medium, as described in Patent Document 1. Triethylamine is also sometimes used as a dispersion medium. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] WO2020 / 203224 Summary of the Invention
[0005] However, the above-mentioned dispersion media are relatively difficult to handle, which poses problems from industrial and environmental standpoints. Therefore, an object of the present invention is to produce a sulfide solid electrolyte using a solvent that is highly safe and can reduce the environmental load.
[0006] The present invention includes a step of mixing a lithium (Li) element source, a phosphorus (P) element source, and a sulfur (S) element source to obtain a raw material composition; A step of calcining the raw material composition to obtain the sulfide; A step of pulverizing a slurry containing a solvent having fluorine atoms and the sulfide; and drying the slurry. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] The present invention will be described below based on its preferred embodiments. The manufacturing method of the present invention relates to a method for manufacturing a sulfide solid electrolyte. This manufacturing method is roughly divided into a step of mixing a lithium (Li) element source, a phosphorus (P) element source, and a sulfur (S) element source to obtain a raw material composition, a step of calcining the raw material composition to obtain the sulfide, a step of pulverizing a slurry containing a solvent having fluorine atoms and the sulfide, and a step of drying the pulverized slurry. Each step will be described below.
[0008] The Li element source may be, for example, lithium sulfide (Li2S). The P element source may be, for example, diphosphorus pentasulfide (P2S5). When the Li element source and / or the P element source is a sulfide, the sulfide may be used as the S element source. A raw material composition is obtained by mixing these compounds. Depending on the type of sulfide solid electrolyte, for example, a halogen (X) element source may be included in the raw material composition. For example, a lithium halide may be used as the X element source. Examples of X include chlorine (Cl), bromine (Br), iodine (I), and fluorine (F).
[0009] The raw material composition obtained by mixing the above-mentioned compounds is subjected to a calcination step. The calcination is preferably carried out in an inert atmosphere or in an atmosphere containing hydrogen sulfide gas. The atmosphere containing hydrogen sulfide gas may be 100% hydrogen sulfide gas or may be a mixed gas of hydrogen sulfide gas and an inert gas such as argon. A sulfide is obtained by the calcination. Regardless of the firing atmosphere, the firing temperature is preferably, for example, from 350° C. to 550° C. The holding time at this temperature is preferably, for example, from 0.5 hours to 20 hours.
[0010] The sulfide thus obtained is not particularly limited in type as long as it is a compound containing sulfur (S), and a known sulfide solid electrolyte can be used. For example, sulfides containing lithium (Li), phosphorus (P), and sulfur (S), sulfides containing lithium (Li), phosphorus (P), germanium (Ge), and sulfur (S), and sulfides containing lithium (Li), phosphorus (P), sulfur (S), and halogen (X), etc. can be mentioned.
[0011] The sulfide to be ground may be a crystalline compound. Alternatively, the sulfide may be a glassy compound. A crystalline compound is a substance in which, when measured by X-ray diffraction (hereinafter also referred to as "XRD"), diffraction peaks due to a crystalline phase are observed.
[0012] The sulfide preferably contains Li, P, S and halogen (X) elements. In the manufacturing method of the present invention using a solvent having fluorine atoms, the affinity between the X and fluorine tends to increase because they are both group 17 elements. This makes it easier for fluorine to be adsorbed on the surface of the solid electrolyte, which protects the surface and reduces the frequency of contact with moisture. As a result, it is presumed that this contributes to suppressing the decrease in ion conductivity. The X is, for example, at least one selected from chlorine (Cl), bromine (Br) and iodine (I), and among these, Cl or Br is preferable, and Cl and Br are particularly preferable. This is because it can improve the lithium ion conductivity. Sulfides, for example, have the formula Li a P.S. b X c(X is at least one halogen element. a can represent a number of 3.0 or more and 6.0 or less. b represents a number of 3.5 or more and 4.8 or less. c represents a number of 0.1 or more and 3.0 or less) is preferably contained in terms of high lithium ion conductivity.
[0013] The sulfide preferably contains a crystal phase having an argyrodite-type crystal structure, since this can enhance the lithium ion conductivity of the solid electrolyte. The argyrodite crystal structure is a crystal structure possessed by a group of compounds derived from a mineral represented by the chemical formula: Ag8GeS6. Whether or not a sulfide has a crystal phase of the argyrodite crystal structure can be confirmed by measurement using XRD. For example, in a diffraction pattern measured by XRD using CuKα1 radiation, the crystal phase of the argyrodite crystal structure shows characteristic diffraction peaks at 2θ=15.3°±1.0°, 17.7°±1.0°, 25.2°±1.0°, 30.0°±1.0°, 30.9°±1.0°, and 44.3°±1.0°. Depending on the elemental species constituting the sulfide, in addition to the above diffraction peaks, characteristic diffraction peaks may be observed at 2θ=47.2°±1.0°, 51.7°±1.0°, 58.3°±1.0°, 60.7°±1.0°, 61.5°±1.0°, 70.4°±1.0°, and 72.6°±1.0°. For identification of the diffraction peaks derived from the argyrodite-type crystal structure, for example, the data of PDF No. 00-034-0688 can be used.
[0014] The above-mentioned sulfide is mixed with a solvent having fluorine atoms to prepare a slurry, and the slurry is wet-pulverized. The sulfide is pulverized to obtain a solid electrolyte, which is the target of the present manufacturing method. Therefore, the sulfide to be pulverized has a particle size larger than that of the solid electrolyte, which is the result of the present manufacturing method. In this sense, in the following description, the sulfide to be pulverized is also referred to as "coarse powder of solid electrolyte."
[0015] Powder pulverization is roughly divided into wet pulverization and dry pulverization, and the present invention employs wet pulverization because it is easier to obtain sulfide powder having a desired particle size by wet pulverization than by dry pulverization.
[0016] Conventionally, when coarse powder of solid electrolyte made of sulfide is wet-milled, toluene or heptane has been used as a solvent. Toluene and heptane are substances that are unlikely to contain water as an impurity, and are therefore suitable as solvents used for wet-milling sulfides that are highly reactive with water. However, toluene and heptane have the disadvantages of being relatively difficult to handle and having a high environmental impact. In order to eliminate this inconvenience, the present inventors have conducted extensive research and found that it is effective to use a solvent having a fluorine atom (hereinafter, this solvent will be referred to as a "fluorine solvent" for convenience). Fluorine solvents have the advantage of being less flammable than toluene and heptane and highly safe for the body. Moreover, when used as a solvent for wet-milling coarse powder of solid electrolyte, wet-milling can be performed successfully in the same way as when toluene or heptane is used.
[0017] As the fluorine solvent, either an inorganic compound or an organic compound can be used. An example of the fluorine solvent made of an inorganic compound is hydrogen fluoride.
[0018] The fluorine solvent made of an organic compound includes a compound in which some or all of the hydrogen atoms in the organic compound used as a solvent are substituted with fluorine atoms. Examples of such organic compounds include those having at least one group selected from the group consisting of an alkyl group, a vinyl group, an aryl group, an ether group, an ester group, a hydroxyl group, an aldehyde group, a carbonyl group, a carboxy group, an amino group, and a sulfo group.
[0019] Specific examples of the organic compound include chain hydrocarbons, cyclic hydrocarbons, aromatic hydrocarbons, vinyl compounds, ethers, esters, alcohols, aldehydes, ketones, organic acids, amines, and sulfonic acids.
[0020] Examples of the fluorine-containing solvent made of a chain hydrocarbon include compounds in which part or all of the hydrogen atoms of a chain alkane, a chain alkene, and a chain alkyne are substituted with fluorine atoms. Examples of the fluorine-containing solvent consisting of a cyclic hydrocarbon include compounds in which some or all of the hydrogen atoms of a cyclic alkane, cyclic alkene, or cyclic alkyne are substituted with fluorine atoms. Examples of fluorine-containing solvents made of aromatic hydrocarbons include compounds in which some or all of the hydrogen atoms bonded to a benzene ring are substituted with fluorine atoms, and compounds in which some or all of the hydrogen atoms of a group bonded to a benzene ring are substituted with fluorine atoms. Examples of the fluorine solvent composed of a vinyl compound include a compound in which some or all of the hydrogen atoms bonded to a vinyl group are substituted with fluorine atoms, and a compound in which some or all of the hydrogen atoms of a group bonded to a vinyl group are substituted with fluorine atoms. Examples of fluorine-containing solvents consisting of ethers include compounds in which some or all of the hydrogen atoms contained in the groups bonded to the ether groups are substituted with fluorine atoms. Examples of fluorine-containing solvents consisting of esters include compounds in which some or all of the hydrogen atoms contained in the groups bonded to the ester groups are substituted with fluorine atoms. The fluorine-containing solvent made of alcohol includes compounds in which some or all of the hydrogen atoms contained in the group bonded to the hydroxyl group are substituted with fluorine atoms. Examples of fluorine-containing solvents consisting of aldehydes include compounds in which some or all of the hydrogen atoms contained in the group bonded to the aldehyde group are substituted with fluorine atoms. The fluorine-containing solvent consisting of a ketone includes compounds in which some or all of the hydrogen atoms contained in the group bonded to the carbonyl group are substituted with fluorine atoms. Examples of fluorine-containing solvents made of organic acids include compounds in which some or all of the hydrogen atoms contained in the organic acid residue are substituted with fluorine atoms. Examples of fluorine-containing amine solvents include compounds in which some or all of the hydrogen atoms contained in the group bonded to the amino group are substituted with fluorine atoms. Examples of fluorine-containing solvents made of sulfonic acids include compounds in which some or all of the hydrogen atoms contained in the group bonded to the sulfo group are substituted with fluorine atoms.
[0021] Among the above-mentioned various fluorine solvents, it is preferable to use fluorides of chain hydrocarbons, aromatic hydrocarbons, vinyl compounds, ethers, esters, alcohols, aldehydes, ketones, organic acids, amines and sulfonic acids, more preferably fluorides of chain hydrocarbons and ethers, and even more preferably fluorides of ethers, in view of the fact that the coarse powder of the solid electrolyte can be successfully wet-pulverized, and that the fluorides are lower in flammability, safer to the body and have a lighter environmental impact.
[0022] Examples of ether fluorides include alkyl fluoroalkyl ethers and difluoroalkyl ethers, with alkyl fluoroalkyl ethers being preferred because of their lower flammability, higher safety for the human body, and lower environmental impact. In particular, alkyl perfluoroalkyl ethers are preferred because of their lower flammability, higher safety for the human body, and lower environmental impact. Examples of alkyl perfluoroalkyl ethers include methyl perfluorobutyl ether and ethyl perfluorobutyl ether.
[0023] Among the above various fluorine solvents, particularly preferred are those which are unlikely to contain water, and in particular those having a water content lower than that of toluene. When sulfides come into contact with water, hydrogen sulfide may be generated, and the use of a fluorine solvent which is unlikely to contain water can reduce the risk of hydrogen sulfide generation. From this viewpoint, the water content of the fluorine solvent is preferably 150 ppm or less, more preferably 120 ppm or less, and even more preferably 100 ppm or less.
[0024] The water content of fluorine solvents can be measured by applying the principle of the Karl Fischer reaction to coulometric titration. Specifically, an electrolyte consisting mainly of iodide ions, sulfur dioxide, and alcohol is placed in an electrolytic cell, and the iodine required for titration is generated internally by electrolysis. The Karl Fischer reaction occurs in the electrolyte, and water reacts with iodine and sulfur dioxide in the presence of a base and alcohol. Meanwhile, in an electrolyte solution containing iodide ions, iodine is generated from the iodide ions at the anode through electrolysis. When the iodine generated here is consumed in the Karl Fischer reaction, the consumption of iodine is detected by the detection electrode, and iodine is generated again at the anode through electrolysis. The amount of water is calculated from the amount of electricity required for the above electrolysis.
[0025] From the viewpoint of further suppressing contact between the coarse particles of the solid electrolyte and water during wet grinding, it is preferable to carry out the wet grinding in an environment with a dew point temperature of −20° C. or less. As described later, when wet grinding is carried out multiple times, it is preferable to carry out all wet grinding in the above-mentioned environment. Also, as described later, when dry grinding is carried out prior to wet grinding, it is preferable to carry out both dry grinding and wet grinding in the above-mentioned environment. In other words, it is preferable to carry out all grinding in the above-mentioned environment, regardless of whether it is dry or wet grinding.
[0026] The above-mentioned various fluorine solvents may be used alone or in combination of two or more kinds. As the solvent for wet grinding, only a fluorine solvent may be used, or a mixed solvent of a fluorine solvent and a solvent other than a fluorine solvent may be used. From the viewpoints of safety and environmental load, the ratio of the fluorine solvent in the mixed solvent is preferably 50% by mass or more, more preferably 70% by mass or more, and even more preferably 90% by mass or more.
[0027] The particle size of the coarse powder of the solid electrolyte dispersed in the fluorine solvent (i.e., the particle size before wet grinding) may be, for example, 0.3 μm or more, 1 μm or more, or 3 μm or more. The particle size here is the volume cumulative particle size D at 50% cumulative volume as measured by a laser diffraction scattering particle size distribution measurement method. 50 This is what I mean.
[0028] In a slurry containing a fluorine solvent and coarse powder of a solid electrolyte, the ratio of the coarse powder of the solid electrolyte in the slurry is preferably set to 3% by mass or more and 40% by mass or less, in order to obtain a sulfide solid electrolyte having a desired particle size. From the viewpoint of making this advantage more prominent, the ratio of the coarse powder of the solid electrolyte in the slurry is more preferably set to 3% by mass or more and 25% by mass or less, and even more preferably set to 7% by mass or more and 20% by mass or less.
[0029] For wet-pulverizing the slurry, various media mills can be used, such as a ball mill, a bead mill, a paint shaker, a homogenizer, and the like. The dispersion media used in the media mill are balls or beads made of various ceramics such as alumina and zirconia. The diameter of the dispersion media can be, for example, 0.1 mm or more and 50 mm or less. In wet grinding using a media mill, the ratio of the dispersion media to the slurry is preferably set to a volume ratio of the media to the slurry present in the grinding chamber (slurry volume / apparent volume of the media) (apparent volume of the media is the volume calculated from the packing density of the media) of 0.2 to 3, in order to obtain a solid electrolyte having a desired particle size. From the viewpoint of making this advantage more prominent, the volume ratio of the media to the slurry is more preferably 0.3 to 2, and even more preferably 0.4 to 1.8. This value varies depending on the grinder and slurry concentration used, and can be set arbitrarily as long as the conditions allow grinding to proceed, and is not particularly limited. The dispersion time by the media mill may be, for example, 10 minutes or more, 15 minutes or more, or 1 hour or more, whereas the dispersion time may be, for example, 60 hours or less, 30 hours or less, or 10 hours or less.
[0030] Wet pulverization may be performed once or twice or more. When wet pulverization is performed twice or more, it is preferable to use pulverization media having a smaller size (diameter) in the latter wet pulverization step in order to perform pulverization efficiently.
[0031] The wet pulverization is preferably carried out until the coarse particles of the solid electrolyte have a particle size suitable for use in a solid-state battery. The preferred particle size of the solid electrolyte after wet pulverization is a volume cumulative particle size D at 50% cumulative volume as determined by a laser diffraction / scattering particle size distribution measurement method. 50 In this case, the thickness is 0.1 μm or more and 20.0 μm or less, particularly 0.3 μm or more and 15.0 μm or less, and especially 0.5 μm or more and 10.0 μm or less.
[0032] In the present invention, prior to wet-pulverization of the coarse particles of the solid electrolyte, dry pulverization can be performed. That is, the coarse particles of the solid electrolyte can be dry-pulverized, the dry-pulverized coarse particles can be mixed with a solvent to prepare a slurry, and the slurry can be wet-pulverized. By performing wet pulverization following dry pulverization, it is possible to improve the pulverization efficiency and easily obtain a sulfide powder having a desired particle size.
[0033] For dry grinding, for example, a jet mill, a ball mill, a rod mill, a vibrating ball mill, a planetary mill, a disk mill, or the like can be used.
[0034] After the above-mentioned wet grinding procedure has been carried out to grind the coarse particles of the solid electrolyte to a desired particle size, the slurry is subjected to solid-liquid separation to obtain a wet solid content, which is then subjected to a drying step to remove the solvent. For drying, for example, hot air drying, drying under reduced pressure, etc. are usable. In order to shorten the drying time, it is preferable to employ a method in which solid-liquid separation by vacuum filtration is followed by drying under reduced pressure. The pressure during reduced pressure drying is preferably an absolute pressure of 10,000 Pa or less, particularly preferably 5,000 Pa or less. There is no particular restriction on the lower limit of the pressure. The temperature is preferably 50°C or higher and 200°C or lower, and more preferably 70°C or higher and 160°C or lower.
[0035] The sulfide solid electrolyte powder thus obtained is sieved as necessary to adjust the particle size to a desired size. The sulfide solid electrolyte powder can be used as a material for forming a solid electrolyte layer, a positive electrode layer, or a negative electrode layer. Specifically, the sulfide solid electrolyte powder can be used in a battery having a positive electrode layer, a negative electrode layer, and a solid electrolyte layer between the positive electrode layer and the negative electrode layer. That is, the sulfide solid electrolyte powder can be used in a so-called solid battery. More specifically, it can be used in a lithium solid battery. The lithium solid battery may be a primary battery or a secondary battery. There is no particular restriction on the shape of the battery, and for example, a laminate type, a cylindrical type, a square type, or the like can be adopted. The term "solid battery" includes a solid battery that does not contain any liquid or gel substance as an electrolyte, as well as an embodiment that contains, for example, 50% by mass or less, 30% by mass or less, or 10% by mass or less of a liquid or gel substance as an electrolyte. EXAMPLES
[0036] The present invention will be described in more detail below with reference to examples. However, the scope of the present invention is not limited to such examples. Unless otherwise specified, "%" means "% by mass".
[0037] Example 1 (1) Preparation of solid electrolyte Li 5.4 P.S. 4.4 Cl 0.8 Br 0.8Li2S powder, P2S5 powder, LiCl powder, and LiBr powder were weighed out so as to obtain the composition. These powders were pulverized and mixed using a ball mill to obtain a mixed powder. The mixed powder was fired to obtain a fired product made of lithium ion conductive sulfide. The firing was performed using a tubular electric furnace. During the firing, 100% pure hydrogen sulfide gas was circulated through the electric furnace at 1.0 L / min. The firing temperature was set to 450°C, and firing was performed for 4 hours. As a result of XRD measurement, it was confirmed that this fired product had a crystal phase with an argyrodite crystal structure.
[0038] (2) Wet grinding of solid electrolyte The fired material was roughly crushed with a mortar and pestle, passed through a 250 μm sieve, and mixed with the solvent shown in Table 1 below to form a slurry with the concentration shown in the table. This slurry was subjected to wet grinding using a paint shaker device (zirconia with a diameter of 2 mm). The beads and the slurry were placed in a grinding container so that the ratio of the apparent volume of the media to the volume of the slurry was 1.5, and wet grinding was performed for 20 minutes. After wet grinding, the slurry was separated into solid and liquid, and the solid content was dried. Drying was performed at 150°C for 20 minutes under a vacuum of -0.09 MPa or less relative to atmospheric pressure. The dried fired material was sieved through a sieve with a mesh size of 53 μm to obtain the desired sulfide solid electrolyte. All of the above steps were performed in an environment with a dew point temperature of -20°C or less.
[0039] [Examples 2 to 6 and Comparative Example 1] In Examples 2 to 6, the fluorine solvents shown in Table 1 below were used. In Comparative Example 1, toluene was used as the solvent. The concentrations of the slurries were as shown in the same table. A sulfide solid electrolyte was obtained in the same manner as in Example 1 except for the above.
[0040] [Table 1]
[0041] In the examples shown in Table 1, it was confirmed that even when a fluorine solvent was used as the solvent for wet-grinding, wet-grinding could be performed in the same manner as when toluene, which is a conventionally used solvent, was used. Although not shown in the table, the inventors confirmed that the lithium ion conductivity of the sulfide solid electrolyte obtained in each example was equivalent to the lithium ion conductivity of the sulfide solid electrolyte obtained in the comparative example. [Industrial Applicability]
[0042] According to the present invention, there is provided a method for producing a sulfide solid electrolyte which is highly safe and can reduce the environmental load.
Claims
1. A step of mixing a lithium (Li) element source, a phosphorus (P) element source, and a sulfur (S) element source to obtain a raw material composition; A step of calcining the raw material composition to obtain a sulfide; A step of pulverizing a slurry containing a solvent having fluorine atoms and the sulfide; and drying the slurry.
2. The method according to claim 1, wherein a concentration of the sulfide in the slurry is 3% by mass or more and 40% by mass or less.
3. The method according to claim 1 or 2, wherein the solvent is an organic compound.
4. The method according to claim 3, wherein the organic compound has at least one group selected from the group consisting of an alkyl group, a vinyl group, an aryl group, an ether group, an ester group, a hydroxyl group, an aldehyde group, a carbonyl group, a carboxy group, an amino group, and a sulfo group.
5. The method according to any one of claims 1 to 4, wherein the step of pulverizing the slurry is carried out in an environment with a dew point temperature of -20°C or lower.
6. The manufacturing method according to any one of claims 1 to 5, wherein the step of pulverizing the slurry is a step of dry-pulverizing the sulfide and mixing the dry-pulverized sulfide with the solvent to prepare the slurry.
7. The method according to claim 1 , wherein the sulfide contains a crystal phase having an argyrodite-type crystal structure.
8. A manufacturing method described in any one of claims 1 to 7, excluding a manufacturing method having a step of applying the slurry between the step of grinding the slurry and the step of drying the slurry.
Citation Information
Patent Citations
Solid electrolyte slurry, method for manufacturing solid electrolyte sheet, solid electrolyte slurry inclusion body, electrode slurry, method for manufacturing electrode sheet, electrode slurry inclusion body, and method for manufacturing all-solid type lithium ion battery
JP2016062709A
Production method of lithium ion conductor, lithium ion conductor, and electricity storage device
JP2020167003A
Sulfur-containing compound, solid electrolyte, and battery
WO2020095937A1
Solid electrolyte
WO2020203224A1